Development of Covalent Ligand-Receptor Pairs to Study the Binding Properties of Nonpeptidic Neurotensin Receptor 1 Antagonists. - Kling, Ralf; Plomer, Manuel; Lang, Christopher; Banerjee, Ashutosh; Hübner, Harald; Gmeiner, Peter (ACS Chemical Biology, 2016)
The neurotensin receptor NTS1 has been suggested to be of pharmaceutical relevance, as it was found to exert modulatory effects on dopaminergic signal transduction and to be involved in tumor progression. Rational drug design of NTS1 receptor ligands requires molecular insights into the binding behavior of a particular lead compound. Although crystal structures of NTS1 have revealed the molecular determinants of peptide-agonist interactions, the binding mode of small-molecule antagonists remains largely unknown. Employing a disulfide-based tethering approach, we developed covalently binding molecular probes. The ligands 1 and 2 are based on the pharmacophore of the nonpeptidic NTS1 antagonist SR142948A, allowing the formation of a disulfide bond to an engineered cysteine residue of NTS1. The position of the covalent bond between Cys127(2.65) and the ligand was used to predict the binding mode of the covalent antagonist 1 and its parent compound SR142948A by molecular dynamics simulations.